Conflits, féminité et identités diasporiques. Le pouvoir de la représentation chez Pratibha Parmar et Gurinder Chadha - Amandine Ducray (Anglophonia)
Ever since they started making films, British Asian female directors Pratibha Parmar and Gurinder Chadha have been aiming to better represent their community and tackle the specific concerns of women from their ethnic groups. Somehow emblematic of the self-representation encouraged by Channel Four in the eighties, such documentaries as Sari Red (Pratibha Parmar, 1988) and I’m British But... (Gurinder Chadha, 1989) brought the peripheral minorities to the centre of the mainstream media. While challenging commonly-held perceptions of citizens from Asian descent, such committed cinema denounced racism, encouraging a spirit of resistance to the traditional ‘Us’ vs ‘Them’ relations of power in British society.Yet as the twenty-first century approached, both directors have embraced a more consensual view of British race relations. Their aim is no longer to denounce but to entertain. Gurinder Chadha abandoned the documentary format as early as 1993. Meant to make everyone laugh, Bhaji on the Beach, her first mainstream comedy, produced a reconciled, all-inclusive portrait of Britain, as did Bend It Like Beckham (2002) and Bride and Prejudice (2004) years later. Taken up by Pratibha Parmar, with Nina’s Heavenly Delights (2006), this hyphenated vision of British-Asian identity highly contrasts with their previous films. This shift in genre has further been accompanied by a shift in conflict: the dichotomy is no longer ethnic but generational, as the opposition between tradition and modernity unravels along the mother-to-daughter relationship.Following a diachronic approach, this article will study the power of representation in Pratibha Parmar’s and Gurinder Chadha’s films in order to explore how the passage from "minority" documentary to "mainstream" comedy has changed the message conveyed to the audience at large—majority and minorities, men and women—as regards both race relations and British identity.